2020
DOI: 10.1002/jsfa.10675
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid ameliorates obesity by preventing energy balance shift in high‐fat diet induced obese mice

Abstract: BACKGROUND: Chlorogenic acid is a type of phenolic acid found in many plants. Chlorogenic acid has an anti-obesity effect with an unclear mechanism. The present study aimed to investigate the regulatory effect of chlorogenic acid on energy balance in high-fat diet (HFD) induced obese C57BL/6J mice administrated 100 mg kg-1 chlorogenic acid for 13 weeks. RESULTS: The consumption of chlorogenic acid ameliorated HFD induced obesity. Chlorogenic acid did not change the physical activity but significantly decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…This study shows that CGA could increase the contents of Bifidobacterium and reduced the Escherichia coli in NAFLD mice, suggesting its promoting effect on GLP-1 secretion may be related with its effect on these gut microbiota. Some studies have shown that CGA could increase the diversity of gut microbiota ( Song et al, 2019 ; Yan et al, 2020 ), while others have shown that the CGA treated mice showed similar microbial structure compared to that of the HFD mice ( He et al, 2020 ). Based on these researches and our study, we speculated that CGA could regulate composition of gut microbiota under different pathological conditions as a different way.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that CGA could increase the contents of Bifidobacterium and reduced the Escherichia coli in NAFLD mice, suggesting its promoting effect on GLP-1 secretion may be related with its effect on these gut microbiota. Some studies have shown that CGA could increase the diversity of gut microbiota ( Song et al, 2019 ; Yan et al, 2020 ), while others have shown that the CGA treated mice showed similar microbial structure compared to that of the HFD mice ( He et al, 2020 ). Based on these researches and our study, we speculated that CGA could regulate composition of gut microbiota under different pathological conditions as a different way.…”
Section: Discussionmentioning
confidence: 99%
“…We administered caffeine and CGA by mixing them in the diet, since it is a commonly used method to administer caffeine and CGA to experimental animals, and the easiest to perform. We applied 0.05% (w/w) of caffeine and 0.1% (w/w) of CGA because they are standard doses with proven positive or negative effects in experimental animals [30,[39][40][41][42][43]. Caffeine inhibited fat accumulation in ICR mice at the same dose and the same method as in the present study [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, chlorogenic acid (100 or 150 mg/ day) reduced oxidative-induced damage and increased antioxidant protection in the inflamed paw skin, and reduced lipid peroxidation in serum (Mitrea et al, 2020). The effect of chlorogenic acid (100 mg/kg BW for 13 weeks) on energy balance in obese mice has been studied recently (He et al, 2020). This compound reduced food intake, increased body temperature, thermal dissipation, brown adipose tissue activity, and improved glucose tolerance.…”
Section: Chlorogenic Acidmentioning
confidence: 99%